STUDI LITERATUR PENGGUNAAN PRODUK BANK SYARIAH DI ERA GEN Z - Pria Mitra Purba; Azrah Cipta Amandha; Chairina Chairina (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research is a literature study that discusses the use of Islamic bank products in the Gen Z era. In research, of course, results will be found on how the Z generation is involved, especially in using Islamic bank products. This literature study aims to discuss more deeply regarding the use of Islamic bank products, what are the advantages and related to the use of Islamic bank products and how the current generation responds to using Islamic bank products. In this study the data obtained through primary data obtained from distributing questionnaires to students with a sample of 12 respondents. This research method also uses a quantitative approach by exploring and studying various existing sources and looking at the current situation and conditions. The results of this study indicate that the use of Islamic bank products has a significant influence on the z generation. This can be seen from the amount of interest and data that has been studied both on previous sources and data reviewed through interviews with respondents.